Involvement of BDNF in Age-Dependent Alterations in the Hippocampus - Von Bohlen Und Halbach, Oliver (Frontiers in Aging Neuroscience, 2010)
It is known since a long time that the hippocampus is sensitive to aging. Thus, there is a reduction in the hippocampal volume during aging. This age-related volume reduction is paralleled by behavioral and functional deficits in hippocampus-dependent learning and memory tasks. This age-related volume reduction of the hippocampus is not a consequence of an age-related loss of hippocampal neurons. The morphological changes associated with aging include reductions in the branching pattern of dendrites, as well as reductions in spine densities, reductions in the densities of fibers projecting into the hippocampus as well as declines in the rate of neurogenesis. It is very unlikely that a single factor or a single class of molecules is responsible for all these age-related morphological changes in the hippocampus. Nevertheless, it would be of advantage to identify possible neuromodulators or neuropeptides that may contribute to these age-related changes. In this context, growth factors may play an important role in the maintenance of the postnatal hippocampal architecture. In this review it is hypothesized that brain-derived neurotrophic factor (BDNF) is a factor critically involved in the regulation of age-related processes in the hippocampus. Moreover, evidences suggest that disturbances in the BDNF-system also affect hippocampal dysfunctions, as e.g. seen in major depression or in Alzheimer disease.